ANALISA AYAT DAN HADIST TENTANG KEWARISAN BEDA AGAMA SERTA REFORMULASI DALAM TATANAN HUKUM INDONESIA - Isnadi, Danil (El-Sirry: Jurnal Hukum Islam dan Sosial, 2023)
Basically, the legal rules applied in examining, adjudicating, and resolving cases regarding civil lawsuits for inheritance lawsuits in each judicial institution refer to KHI article 171, articles 1 and 2 in conjunction with Article 49 of Law No. 7 of 1989, as well as the arguments of the Qur'an An-Nisa's letter, 4:141, HR. Al-Bukhori and Muslim, so that the Islamic personality is determined by the heir and ignores wills that cannot be proven, and the heir and heirs must both be Muslims, whereas in 1998 the Supreme Court with cassation case register no: 368 K/AG/1995 When making decisions using legal rules, if the parents have a different religion than the child, they are considered to have left a will, which is called a mandatory will. And took the decision to grant non-Muslim heirs the rights based on the mandatory will by referring to the opinion of some scholars such as Yusuf Al-Qadhowi who argued that non-Muslim heirs would receive the inheritance of Muslim heirs through the mandatory will.